Dampak Pembangunan Jembatan Sei Alalak Terhadap Kondisi Kegiatan Ekonomi Pedagang di Sekitar Proyek - Ratu Tiara Wulandari; Muhammad Effendi (PPJP Universitas Lambung Mangkurat, 2022)
This research was conducted to find out (1) What is the economic condition of the merchant community before the Sei Alalak Bridge construction project, (2) What is the economic impact of the merchant community during the Sei Alalak Bridge construction project, (3) What is the expectation of the merchant community for the economic conditions after the Sei Alalak Bride construction project.The method used is descriptive. Types and sources of data are primary and secondary. Primary data was obtained through interviews using questionnaires and secondary data obtained from literature study data sources and the Office of the Regional Development Planning Board Batola. Based on the study results, an analysis of the impact before the construction of the Sei Alalak Bridge on the economic condition can be seen from the number of works owned by traders are also in good condition where traders have a workforce of 1-4 people. It can also be seen from the number of buyers where in a day can get more than 150 buyers; the also can be seen from the merchant’s income where the highest is more than Rp 1.500.000 as many as 42 people and the lowest is less than Rp 500.000 as many as 11 people. On the impact when the construction of the Bridge has also declined the economic situation can be seen from the distribution channel of goods sometimes hampered, in terms of the number of workers also decreased to 1-3 people, then the buyers also dropped dramatically because 68% of traders only got buyers less than 50 people. There is a decrease in income for some traders at the time of the project, while in terms of expenditure is enough to make traders overwhelmed because they have to provide for their families and send their children to school, and the average expenditure on food is more than Rp 1.000.000, for the average cost of education more than Rp 500.000. The most impacting was the income of traders, a decrease in trader income, where the highest income of more than Rp 1.500.000 was reduced to 29 people, and the lowest income of less than Rp 500.000 increased to 17 people. From the economic condition of the merchant community around the project at Alalak Kayu Tangi Ujung to recover, as before the construction of the project and even expect economic conditions around the Sei Alalak Bridge to increase so that the traders can feel the positive impact of the development.